Pesantren Curriculum: A Case Study of Al-Bahjah Islamic Boarding School - Az Zahro, Fatimah; Nurlaela, Nurlaela (Progressive of Cognitive and Ability, 2024)
This study examines the implementation of curriculum management at the Tafaqquh level at Pondok Pesantren Al-Bahjah, a non-formal Islamic education institution oriented towards strengthening morals and mastering the knowledge of Islamic law, especially Arabic. Using a qualitative case study approach, data were collected through observation, interviews, and documentation. Analysis was conducted using Miles and Huberman's interactive model to understand the learning and evaluation process. The research found that the Tafaqquh level has a distinctive Arabic-based curriculum with classical learning methods such as lectures, speaking practice, writing, and the use of audio-visual media. Students are evaluated continuously through formative and summative exams to ensure competency achievement. The findings show that the main obstacle is the santri's low understanding of the Arabic material delivered by the teacher. However, strategies such as muhadhoroh activities and communicative approaches are able to improve santri language skills. This study confirms the relevance of pesantren as a center for character education and the development of religious knowledge that can adapt to the times' challenges.